Bloody Mary. Volume 2 - Samamiya, Akaza (Samamiya, Akaza. Buraddi mearī., 2016)
Bloody Mary, a vampire with a death wish, has spent the past 400 years chasing down a modern-day exorcist named Maria who is thought to have inherited The Blood of Maria and is the only one who can kill Mary. To Mary's dismay, Maria doesn t know how to kill vampires. Desperate to die, Mary agrees to become Maria's bodyguard until Maria can find a way to kill him. Maria never knew he possessed the Power of Exorcism, which can kill vampires, but with Mary's help, his research unearths the Red Memories that he has suppressed for so long. At the same time, the door to Mary's own missing memories is thrust forcefully open. Where do Maria's Red Memories and Mary's past intersect and what truths await them?"